2008
DOI: 10.3141/2089-03
|View full text |Cite
|
Sign up to set email alerts
|

Location Routing Approach for the Humanitarian Prepositioning Problem

Abstract: Events such as Hurricanes Katrina and Rita in 2005 have highlighted the need to understand network disruptions, in particular in the humanitarian supply chain. Humanitarian supply logistics cannot be improvised at the time of the emergency since little can be done after a disruption occurs. Therefore, special attention should be given to preparedness efforts and the design of the supply chain network. Inventory prepositioning is one of the strategies in the preparedness stage that enhances postdisaster respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 19 publications
0
82
0
3
Order By: Relevance
“…Ukkusuri and Yushimito (2008) presented a single stage model incorporate the idea of the most reliable path in a facility location problem in which used in solving the inventory prepositioning problem for humanitarian supply chains. Another single stage model proposed by Jia et al (2005) showed how the general large-scale emergency facility location problem leads to covering, P-median, and Pcenter problems.…”
Section: The Characteristics Of Problem Formulationmentioning
confidence: 99%
“…Ukkusuri and Yushimito (2008) presented a single stage model incorporate the idea of the most reliable path in a facility location problem in which used in solving the inventory prepositioning problem for humanitarian supply chains. Another single stage model proposed by Jia et al (2005) showed how the general large-scale emergency facility location problem leads to covering, P-median, and Pcenter problems.…”
Section: The Characteristics Of Problem Formulationmentioning
confidence: 99%
“…The most recent integrated model of this type in the area of service level optimization is published by Liu et al [47]. Among the humanitarian studies, three of the published contributions on LRP worked on disaster relief cases in a multi-objective basis [48][49][50][51]. All of the mentioned papers aimed at the design of distribution networks for relief goods and services in times of disaster.…”
Section: Location Routing Problemsmentioning
confidence: 99%
“…Several authors also integrate the stocking level and location decisions with short-term decisions. Important examples include the work of Ozbay and Ozguven (2007), Ukkusuri and Yushimito (2008), and Rawls and Turnquist (2012). In order to minimize "stock out" probability, Ozbay and Ozguven (2007) developed an inventory model to determine stocking quantities subject to uncertain demands and delivery schedule at a relief location.…”
Section: Short-term Responsementioning
confidence: 99%
“…In order to minimize "stock out" probability, Ozbay and Ozguven (2007) developed an inventory model to determine stocking quantities subject to uncertain demands and delivery schedule at a relief location. Ukkusuri and Yushimito (2008) addressed location determination problem aiming to minimize the probability of uncovered demand points. Rawls and Turnquist (2012) addressed the prepositioning network and short-term distribution decisions simultaneously.…”
Section: Short-term Responsementioning
confidence: 99%